2013
DOI: 10.5852/ejt.2013.66
|View full text |Cite
|
Sign up to set email alerts
|

On the Bennelongia barangaroo lineage (Crustacea, Ostracoda) in Western Australia, with the description of seven new species

Abstract: The ostracod genus Bennelongia De Deckker & McKenzie, 1981 is endemic to Australia and New Zealand. Extensive sampling in Western Australia (WA) revealed a high specific and largely undescribed diversity. Here, we describe seven new species belonging to the B. barangaroo lineage: B. timmsi sp. nov., B. gnamma sp. nov., B. hirsuta sp. nov., B. ivanae sp. nov., B. mcraeae sp. nov., B. scanloni sp. nov. and B. calei sp. nov., and confirm the presence of an additional species, B. dedeckkeri, in WA. For five of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 437 publications
(17 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Low barcode success rates have also been reported for cladocerans and rotifers, and most barcode studies on these groups are taxonomically limited in scope (Elías-Gutiérrez, Martínez-Jerónimo, et al, 2008;Hwang, Dahms, Park, & Lee, 2013;Jeffery, Elías-Gutiérrez, & Adamowicz, 2011;Proios et al, 2014). Although DNA barcodes successfully discriminate other taxa of freshwater zooplankton such as ostracods (Cohuo-Durán, Elías-Gutiérrez, & Karanovic, 2013;Martens, Halse, & Schoen, 2015), no broad barcoding studies have been undertaken.…”
mentioning
confidence: 99%
“…Low barcode success rates have also been reported for cladocerans and rotifers, and most barcode studies on these groups are taxonomically limited in scope (Elías-Gutiérrez, Martínez-Jerónimo, et al, 2008;Hwang, Dahms, Park, & Lee, 2013;Jeffery, Elías-Gutiérrez, & Adamowicz, 2011;Proios et al, 2014). Although DNA barcodes successfully discriminate other taxa of freshwater zooplankton such as ostracods (Cohuo-Durán, Elías-Gutiérrez, & Karanovic, 2013;Martens, Halse, & Schoen, 2015), no broad barcoding studies have been undertaken.…”
mentioning
confidence: 99%
“…Males with different valve shape have slightly different morphologies in the rpp, but as this could be part of a normal range of variability, its occurrence should be checked on longer series of dissections. Bennelongia timmsi Martens et al, 2013 also showed significant variability in the shape of the Rpp .…”
Section: Morphology Ecology and Distributionmentioning
confidence: 98%
“…Most species also with very pronounced anterior lV/rV overlap, most pronounced of all lineages in this genus. Some species with an inner 'eyelet' in the anterior part of the RV, close to the lapel, just as in the species of the B. barangaroo lineage (see Martens et al 2013), to which this lineage is most closely related. Fig …”
Section: Diagnosis Of the B Nimala-lineagementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the development of a chaetotaxal model (Broodbakker & Danielopol 1982;Martens 1987;Meisch 2000), the advancement of dissection techniques, higher magnification compound microscopes and scanning electron microscopy have since enabled the illustration of a larger suite of taxonomic characters (e.g. Halse & McRae 2004;Savatenalinton & Martens 2009), while the use of genetic species identification methods in new species descriptions (Martens et al 2012(Martens et al , 2013Shearn et al 2012) further adds to the available set of taxonomic characters. The resulting disparity of character sets between old and new descriptions has often made comparison of closely related species difficult during species diagnosis.…”
Section: Introductionmentioning
confidence: 99%